Question
Thu September 03, 2009 By:

Inverse Trignometric Functions

Expert Reply
Sat September 05, 2009

sin (sin-1(1/5) + cos-1(x)) = 1

(sin-1(1/5) + cos-1(x)) = sin-1(1)

sin-1(1/5) + cos-1(x) = /2

Now by using the property,

sin-1(x) + cos-1(x) =  /2

⇒ x = 1/5

Similarly try the second question.

In case of multiple questions within a query, please post each question individually and let us know where you are getting stuck so that we would be able to explain things better.

Home Work Help